Analisis Gaya Kepemimpinan Transformasional Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan di SD Islam Al Azhar 71 Kota Pangkalpinang - Mutiara Haq (4, 2025)
This study highlights the leadership style of the principal at SD Islam Al Azhar 71 Pangkalpinang and its impact on teacher performance and student achievement. The results revealed that transformational leadership was the most dominant and effective approach in improving the quality of education at the school. Transformational leadership is reflected in the charisma, inspirational motivation, intellectual stimulation, and individual attention provided by the principal to teachers and students. Through this approach, the school successfully recorded significant improvements over a five-year period, as evidenced by a surge in student numbers from 89 to 325, increased student academic and non-academic achievement, and increased teacher motivation and performance. Although elements of both situational and laissez-faire leadership styles emerged in some instances, they were not dominant and were more complementary. This demonstrates that transformational leadership can provide clear direction while creating a school climate conducive to student and teacher development. This success also demonstrates how a new Islamic school can build a positive reputation with the right leadership approach. In line with this, a strategy for increasing youth activities at mosques in Bangka Regency was also developed, including youth development through mosques, increasing the number and quality of members, strengthening relationships between mosque administrators and youth, fostering attitudes and behaviors, strengthening social activities, expanding organizational networks, developing types of activities, and utilizing digital technology. These efforts emphasize that appropriate leadership and development can be key to the success of educational institutions and religious organizations. Abstrak Studi ini menyoroti gaya kepemimpinan kepala sekolah di SD Islam Al Azhar 71 Pangkalpinang serta dampaknya terhadap kinerja guru dan prestasi siswa. Hasil penelitian mengungkapkan bahwa gaya kepemimpinan transformasional menjadi pendekatan paling dominan sekaligus efektif dalam mengembangkan mutu pendidikan di sekolah tersebut. Kepemimpinan transformasional tercermin melalui kharisma, motivasi inspirasional, stimulasi intelektual, serta perhatian individual yang diberikan kepala sekolah kepada guru dan siswa. Melalui pendekatan ini, sekolah berhasil mencatatkan peningkatan signifikan dalam kurun waktu lima tahun, yang terlihat dari lonjakan jumlah siswa dari 89 menjadi 325, bertambahnya prestasi akademik maupun non-akademik siswa, serta meningkatnya motivasi dan kinerja para guru. Meskipun dalam beberapa kondisi muncul elemen gaya kepemimpinan situasional maupun laissez-faire, namun keduanya tidak dominan dan lebih sebagai pelengkap. Hal ini menunjukkan bahwa kepemimpinan transformasional mampu memberikan arah yang jelas sekaligus menciptakan iklim sekolah yang kondusif bagi perkembangan siswa dan guru. Keberhasilan ini juga memperlihatkan bagaimana sekolah Islam baru dapat membangun reputasi positif dengan pendekatan kepemimpinan yang tepat. Sejalan dengan itu, formulasi strategi peningkatan aktivitas remaja masjid di Kabupaten Bangka turut dikembangkan, meliputi pembinaan remaja melalui masjid, peningkatan jumlah dan kualitas anggota, mempererat hubungan antara takmir dan remaja masjid, pembinaan sikap dan perilaku, penguatan kegiatan sosial, perluasan jaringan organisasi, pengembangan jenis aktivitas, serta pemanfaatan teknologi digital. Upaya ini menegaskan bahwa kepemimpinan dan pembinaan yang tepat dapat menjadi kunci keberhasilan lembaga pendidikan maupun organisasi keagamaan.